Nilai Pendidikan Karakter dalam Cerita Malaikat Jatuh Karya Clara Ng - Wiwik Surya Utami (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Literary creation is the process of producing a work of art. Through literature, a person can produce imaginative works based on experiences and lessons learned in life. This study focuses on the values of character education in the short story Malaikat Jatuh, and the research data consists of the text found in the short story Malaikat Jatuh by Clara Ng. The research method used in this study is qualitative; fundamentally, qualitative research focuses on content analysis—that is, examining content to understand the values within the research object, which will be described verbally. This study identified 10 character education values: piety, honesty, wisdom, leadership, compassion, steadfastness, diligence, self-confidence, patience, and responsibility. The strength of short stories in instilling character values lies in their ability to convey moral messages in an engaging, easily understandable way, as these messages significantly influence readers’ mindsets and serve as a guide in daily life